Constituents of Gutierrezia mandonii (Asteraceae) - Alarcón, Silvia Rosana (2009)
The genus Gutierrezia (Asteraceae) includes approximately 25 species which occur exclusively in the arid areas of América. Eighth species, Gutierrezia baccharoides Sch. Bip., Gutierrezia gilliesii Griseb., Gutierrezia isernii (Phil.) Phil., Gutierrezia mandonii (Sch. Bip.) Solbrig, Gutierrezia pulviniformis Cabrera, Gutierrezia repens Griseb., Gutierrezia solbrigii Cabrera, and Gutierrezia spathulata (Phil.) Kurtz, grow in Argentina (Freire, 1999). G. mandonii is a resinous shrub which grows naturally in the arid areas of northern Argentina and southern Bolivia (Cabrera, 1978). The aerial parts of G. mandonii were collected during the flowering period in Salta, Argentina, on January 2004. The plant was identified by Ing. Julio Tolaba. A voucher specimen (no 3414) was deposited at the Museo de la Facultad de Ciencias Naturales, Universidad Nacional de Salta.